(untitled) (Poornaprajna International Journal of Management, Education & Social Science (PIJMESS), 2025)
Purpose: This paper examines the factors contributing to women’s increasing participation in the workforce, particularly in the corporate sector, and explores the challenges and opportunities they face in achieving professional and personal success. Key questions include: (a) Is the representation of women in the corporate space encouraging? (b) Are women performing well in corporate roles? (c) Are there women-friendly organizations that support their family and professional needs? Methodology: The study explores various issues related to women employees in the corporate space, including their representation, performance, and the role of organizational policies in empowering women. It also evaluates the extent to which organizations address women’s dual responsibilities of family and career. Findings: The paper highlights factors driving women’s entry into the job market, including economic pressures and aspirations for academic and professional achievement. However, it also identifies significant challenges, such as the glass ceiling and limited organizational initiatives aimed at supporting women employees. Implications: This research emphasizes the need for proactive measures by organizations to create inclusive, supportive, and empowering environments for women. It calls for discussions on improving workplace practices to ensure equity and better opportunities for women in corporate spaces. Originality/Value: This paper contributes to the ongoing dialogue about women’s empowerment and workplace inclusivity by addressing gaps in representation, organizational support, and professional growth opportunities for women in corporate sectors. Type of Paper: This is an exploratory paper that examines the role of women in India’s corporate sector. It analyzes secondary data to explore trends, challenges, and organizational practices. The study aims to gain insights rather than test hypotheses. Its focus is on understanding women’s participation and progress in corporate spaces.